Gender stereotypes of personality : universal and accurate? - Löckenhoff, Corinna E. (Array, 2014)
Numerous studies have documented subtle but consistent sex differences in self-reports and observer-ratings of five-factor personality traits, and such effects were found to show well-defined developmental trajectories and remarkable similarity across nations. In contrast, very little is known about perceived gender differences in five-factor traits in spite of their potential implications for gender biases at the interpersonal and societal level. In particular, it is not clear how perceived gender differences in five-factor personality vary across age groups and national contexts and to what extent they accurately reflect assessed sex differences in personality. To address these questions, we analyzed responses from 3,323 individuals across 26 nations (mean age = 22.3 years, 31% male) who were asked to rate the five-factor personality traits of typical men or women in three age groups (adolescent, adult, and older adult) in their respective nations. Raters perceived women as slightly higher in openness, agreeableness, and conscientiousness as well as some aspects of extraversion and neuroticism. Perceived gender differences were fairly consistent across nations and target age groups and mapped closely onto assessed sex differences in self- and observer-rated personality. Associations between the average size of perceived gender differences and national variations in sociodemographic characteristics, value systems, or gender equality did not reach statistical significance. Findings contribute to our understanding of the underlying mechanisms of gender stereotypes of personality and suggest that perceptions of actual sex differences may play a more important role than culturally based gender roles and socialization processes. [eng]